Summary report: Pingree Park research retreat - Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 1985)
On June 19-21, 1985 a retreat was held at the CSU Mountain Campus of Pingree Park for students and faculty involved with current research projects. The following is a compilation of attendees, presentations, and summary reports of the small group sessions.
Keywords: Atmosphere -- Research; Meteorology -- Research